2003
DOI: 10.1124/jpet.103.052365
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol Prevents Tumor Necrosis Factor-α-Induced Cell Death by Suppression of Phosphatase and Tensin Homolog Deleted from Chromosome 10 Phosphorylation and Activation of Akt/Cyclic AMP Response Element-Binding Protein Phosphorylation

Abstract: This study examines the signaling mechanism by which cilostazol prevents neuronal cell death. Cilostazol (ϳ0.1-100 M) prevented tumor necrosis factor-␣ (TNF-␣)-induced decrease in viability of SK-N-SH and HCN-1A cells, which was antagonized by 1 M iberiotoxin, a maxi-K channel blocker. TNF-␣ did not suppress the viability of the U87-MG cell, a phosphatase and tensin homolog deleted from chromosome 10 (PTEN)-null glioblastoma cell, but it did decrease viability of U87-MG cells transfected with expression vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…When the expression of tissue cAMP in the proximal ascending aorta including aortic sinus was determined by immunohistochemistry, a significant elevation of cAMP expression was identified in the mice fed a 0.2% w/w cilostazol-supplemented high fat diet (data not shown). Most recently, cilostazol was found to increase the K ϩ currents in SK-N-SH cells (human brain neuroblastoma, Hong et al, 2003) and human coronary artery endothelial cells (K. W. Hong, unpublished data) by activating the maxi-K channels. It has been suggested that activation of cAMP-dependent protein kinase A by cAMP-elevating agents, such as forskolin and dibutyryl cAMP, inhibits TNF-␣-induced NF-B-dependent reporter gene expression and reduces endogenous NF-B-dependent adhesion molecule and chemokine expression (Ollivier et al, 1996;Aizawa et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…When the expression of tissue cAMP in the proximal ascending aorta including aortic sinus was determined by immunohistochemistry, a significant elevation of cAMP expression was identified in the mice fed a 0.2% w/w cilostazol-supplemented high fat diet (data not shown). Most recently, cilostazol was found to increase the K ϩ currents in SK-N-SH cells (human brain neuroblastoma, Hong et al, 2003) and human coronary artery endothelial cells (K. W. Hong, unpublished data) by activating the maxi-K channels. It has been suggested that activation of cAMP-dependent protein kinase A by cAMP-elevating agents, such as forskolin and dibutyryl cAMP, inhibits TNF-␣-induced NF-B-dependent reporter gene expression and reduces endogenous NF-B-dependent adhesion molecule and chemokine expression (Ollivier et al, 1996;Aizawa et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, cilostazol inhibits high glucose-mediated endothelial-neutrophil adhesion by decreasing adhesion molecule expression via NO production. It also prevents remnant lipoprotein particleinduced monocyte adhesion to endothelial cells by suppressing the expression of adhesion molecules and monocyte chemoattractant protein-1 via a lectin-like receptor for oxidized low-density lipoprotein receptor activation 21) . Furthermore, cilostazol suppresses superoxide production and the expression of adhesion molecules in human endothelial cells via the mediation of cAMP-dependent protein kinase-mediated Maxi-K channel activation 22,23) .…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [11] reported a protective effect of cilostazol against lipopolysaccharide (LPS)-induced apoptosis in human umbilical vein endothelial cells (HUVECs). Hong et al [12] demonstrated the ability of cilostazol to prevent tumor necrosis factor-α (TNF-α)-induced cell death in human neuroblastoma cells. An in vivo study in an animal model of middle cerebral artery occlusion and reperfusion also provided evidence of the protective effect of cilostazol against cerebral infarct through anti-apoptotic actions.…”
Section: Introductionmentioning
confidence: 99%